(untitled) (Scottish Historical and Archaeological Internet Reports, 2012)
Eleven different taxa of snail shells represent a group that would be typical of moist rubble habitats on generally acid soils very similar to what would be expected from modern fauna at the site. Charcoal data places the site places the site within or close to areas of birch, hazel and willow scrub. The environment would not be very different to that found in wooded valleys and sheltered areas of the coast below 200 m today.